Using PCM, an Experimental Study on Solar Stills Coupled with and without a Parabolic Trough Solar Collector - Jaber, Hazim Jassim; Rishak, Qais A.; Abed, Qahtan A. (Basrah Journal for Engineering Sciences, 2021)
Performance a double slope of the solar still Integrated With or without parabolic trough collector is investigated experimentally. To improve the output of a double slope solar still, a number of initiatives have been undertaken, using wax as a phase change material (PCM) with a parabolic trough collector. A parabolic trough collector (PTC) transfers incident solar energy to the solar still through a water tube connected to a heat exchanger embedded in used microcrystalline wax. Experiments were carried out after orienting the basin to the south and holding the water depth in the basin at 20 mm. According to the results obtained, the solar stills with parabolic trough collector have higher temperatures and productivity than solar stills without parabolic trough collector, as well as the ability to store latent heat energy in solar still, allowing fresh water to condense even after sunset. In addition, the parabolic trough collector with phase change material in the double slope solar improves productivity by 37.3 % and 42 %, respectively.